Biomass and potential nutrient removal by harvesting in short-rotation plantations - Yamada, M.; Toma, T.; Hiratsuka, M.; Morikawa, Y. (Center for International Forestry Research, 2004)
Data on standing biomass, mean annual increment of carbon stock, and nutrient accumulation in 40 industrial plantations at 21 sites in 11 countries are summarised. Aboveground biomass and mean annual increment of carbon near the harvest age, of these plantations ranged from 44 to 324 t ha-1 and from 3.1 to 22.9 tC ha-1 yr-1, respectively. Plantations managed on a short rotation are expected to accumulate carbon rapidly. However, there are large variations of biomass accumulation depending on site conditions. There is concern about the potential decrease of productivity caused by nutrient loss by intensive and repeated harvesting. It is important to determine the nutrients removed and conserve them as much as possible to prevent productivity loss and for sustainable management of industrial plantations. Careful management of the nutrient cycle through residue retention and fertiliser application is necessary to maintain high productivity.